Synthesis and characterization of nanofluids from the biosynthesis of nanoparticles and their evaluation in solar thermal systems - Asmat-Campos, David (2020)
ABSTRACT The objective of the study was to evaluate diverse and known types of heat transfer fluids (water, oil and glycerin) commonly used in solar thermal systems, in this work denoted as base fluids, with respect to them, but with the addition of biosynthesized metal nanoparticles. It was considered a prototype of solar heating systems by thermosiphon in the application-experimental phase assisted by halogen light (with wavelengths ranging from deep infrared to violet). The process of biosynthesis or green synthesis of silver nanoparticles (NP Ag) was from the precursor of silver nitrate (AgNO3) and using as a reducer the alcoholic extract from agroindustrial residues of the wine production, obtaining colloids with high monodispersity and with sizes between 30 and 40 nm. (spherical geometry). The results suggest a greater increase in heat absorption capacity when biosynthesized silver nanoparticles are added to the oil, which managed to have a heat capacity of 3519.41 J/kg°C.